TRPC5 Channel Inhibition Protects Podocytes in Puromycin-Aminonucleoside Induced Nephrosis Models - Zhou, Yiming; Kim, Choah; Pablo, Juan Lorenzo B.; Zhang, Fan; Jung, Ji Yong; Xiao, Li; Bazua-Valenti, Silvana; Emani, Maheswarareddy; Hopkins, Corey R.; Weins, Astrid; Greka, Anna (Frontiers in Medicine, 2021)
Podocyte injury and the appearance of proteinuria are key features of several progressive kidney diseases. Genetic deletion or selective inhibition of TRPC5 channels with small-molecule inhibitors protects podocytes in rodent models of kidney disease, but less is known about the human relevance and translatability of TRPC5 inhibition. Here, we investigate the effect of TRPC5 inhibition in puromycin aminonucleoside (PAN)-treated rats, human iPSC-derived podocytes, and kidney organoids. We first established that systemic administration of the TRPC5-specific inhibitor AC1903 was sufficient to protect podocyte cytoskeletal proteins and suppress proteinuria in PAN-induced nephrosis rats, an established model of podocyte injury. TRPC5 current was recorded in the human iPSC-derived podocytes and was blocked by AC1903. PAN treatment caused podocyte injury through TRPC5 channel in human iPSC-derived podocytes and kidney organoids. Inhibition of TRPC5 channel reversed the effects of PAN-induced injury in human podocytes in both 2D and 3D culture systems. Taken together, these results revealed the relevance of TRPC5 channel inhibition in puromycin-aminonucleoside induced nephrosis models, highlighting the potential of this therapeutic strategy for patients.